2019
DOI: 10.1111/ejn.14424
|View full text |Cite
|
Sign up to set email alerts
|

Feedback inhibition derived from the posterior parietal cortex regulates the neural properties of the mouse visual cortex

Abstract: Feedback regulation from the higher association areas is thought to control the primary sensory cortex, contribute to the cortical processing of sensory information, and work for higher cognitive functions such as multimodal integration and attentional control. However, little is known about the underlying neural mechanisms. Here, we show that the posterior parietal cortex (PPC) persistently inhibits the activity of the primary visual cortex (V1) in mice. Activation of the PPC causes the suppression of visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
0
22
2
Order By: Relevance
“…However, results reported by different research groups are diverse or even opposite. For example, some authors find out that top-down influence can facilitate the responses of V1 neurons and thus enhance their orientation or direction selectivity (Wang et al, 2000(Wang et al, , 2007(Wang et al, , 2010Galuske et al, 2002;Huang et al, 2007;Tong et al, 2011;Moldakarimov et al, 2014;Zhang et al, 2014;Nurminen et al, 2018;Keller et al, 2020), whereas others report that top-down influence is suppressive and lowers neuronal response in the low-level visual cortex (Murray et al, 2002;Alink et al, 2010;Nassi et al, 2013;Klein et al, 2014;Hishida et al, 2019;Maniglia et al, 2019;Ranson et al, 2019). A critical way to reconcile these contradictions is to determine the cell type of feedback neurons as well as the neurotransmitter system used by the feedback circuitry.…”
Section: Mechanisms Of Top-down Influencementioning
confidence: 99%
See 1 more Smart Citation
“…However, results reported by different research groups are diverse or even opposite. For example, some authors find out that top-down influence can facilitate the responses of V1 neurons and thus enhance their orientation or direction selectivity (Wang et al, 2000(Wang et al, , 2007(Wang et al, , 2010Galuske et al, 2002;Huang et al, 2007;Tong et al, 2011;Moldakarimov et al, 2014;Zhang et al, 2014;Nurminen et al, 2018;Keller et al, 2020), whereas others report that top-down influence is suppressive and lowers neuronal response in the low-level visual cortex (Murray et al, 2002;Alink et al, 2010;Nassi et al, 2013;Klein et al, 2014;Hishida et al, 2019;Maniglia et al, 2019;Ranson et al, 2019). A critical way to reconcile these contradictions is to determine the cell type of feedback neurons as well as the neurotransmitter system used by the feedback circuitry.…”
Section: Mechanisms Of Top-down Influencementioning
confidence: 99%
“…However, the characteristics of feedback influence on the responses of V1 neurons remains in debate (Han and VanRullen, 2016). Some authors propose that top-down influence produces excitatory feedback inputs and facilitate neuronal response in the V1 area (Wang et al, 2000(Wang et al, , 2007(Wang et al, , 2010Huang et al, 2004;Liang et al, 2007;Tong et al, 2011;Chen et al, 2014;Zhang et al, 2014;van Loon et al, 2015;Kok et al, 2016;Pafundo et al, 2016;Yang X. et al, 2016;Baumgartner et al, 2018;Huh et al, 2018), whereas others suggest that top-down influence exert suppressive impacts on neurons in the low-level visual areas (Roland et al, 2006;Chalk et al, 2010;Nassi et al, 2013Nassi et al, , 2014Klein et al, 2014;Hishida et al, 2019;Maniglia et al, 2019). Still, others report bidirectional top-down effects of both suppression and enhancement (Gazzaley et al, 2005;Johnson and Johnson, 2009;Cox et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…35 On the other hand, the PPC is known to play essential roles in selective attention and reward-history bias 27,36 and regulates the response properties of V1 neurons. [37][38][39] Recent imaging studies have examined visual perceptual behavior during a go or no-go detection task and found that task requirements 40 heavily modulate visual responses in the PPC and that heterogeneous recruitment of V1 neurons plays an important role in visual detection. 40,41 Together, these studies support the notion that the V1 and PPC create distinct cortical states at the population level that integrate task-relevant external signals 42 with internal states for subjective detection performance.…”
Section: Introductionmentioning
confidence: 99%
“…Visual impairment can cause behavioral abnormalities in human and mice related to hypersensitivity to sensory stimuli. Moreover, the visual cortex eceives feedback projections from auditory and somatosensory cortex as well as from motor and multisensory cortices [22,[52][53][54][55][56]. However, Trpm1 −/− mice did not show hypersensitivity to sensory stimuli, which is observed in visually impaired animals as well as in human patients [20][21][22][23][24][25][26][27][28][29], at least for thermal perception and auditory responses (Fig.…”
Section: Discussionmentioning
confidence: 94%